1971
DOI: 10.1002/1097-0142(197108)28:2<467::aid-cncr2820280228>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Malignant histiocytosis: A case of generalized histiocytosis with infiltration of Langerhans' granule-containing histiocytes

Abstract: A 9‐year‐old girl with leukemic infiltration of cells characterized by indented nuclei and abundant faintly acidophilic cytoplasm was autopsied. Electron microscopic studies of the cervical lymph nodes and tumor nodules in the liver and kidney (fixed in formalin solution for 3 years) together with the specimens taken from the cutaneous eruptions at autopsy demonstrated that the proliferating cells frequently contained Langerhans' granules in the cytoplasm. Accordingly, this case was thought to be a disease wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
1

Year Published

1973
1973
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(19 citation statements)
references
References 23 publications
0
17
1
1
Order By: Relevance
“…LC, -as defined by their unique cytoplasmic organelles, -the Langerhans cell (or Birbeck) granules, were detected in various mesodermal tissues (Kondo 1969, Hoshino et al 1970, Breathnach 1977) and, furthermore, LC granules were found to be present in certain histiocytic cells in histiocytosis X (Basset & Turiaf 1965, Cancilla et al 1967) and occasionally, in malignant ceils of patients with malignant histiocytosis (Imamura et al 1971) and leukemic reticuloendotheliosis (Shamoto et al 1976). LC, -as defined by their unique cytoplasmic organelles, -the Langerhans cell (or Birbeck) granules, were detected in various mesodermal tissues (Kondo 1969, Hoshino et al 1970, Breathnach 1977) and, furthermore, LC granules were found to be present in certain histiocytic cells in histiocytosis X (Basset & Turiaf 1965, Cancilla et al 1967) and occasionally, in malignant ceils of patients with malignant histiocytosis (Imamura et al 1971) and leukemic reticuloendotheliosis (Shamoto et al 1976).…”
Section: Introductionmentioning
confidence: 99%
“…LC, -as defined by their unique cytoplasmic organelles, -the Langerhans cell (or Birbeck) granules, were detected in various mesodermal tissues (Kondo 1969, Hoshino et al 1970, Breathnach 1977) and, furthermore, LC granules were found to be present in certain histiocytic cells in histiocytosis X (Basset & Turiaf 1965, Cancilla et al 1967) and occasionally, in malignant ceils of patients with malignant histiocytosis (Imamura et al 1971) and leukemic reticuloendotheliosis (Shamoto et al 1976). LC, -as defined by their unique cytoplasmic organelles, -the Langerhans cell (or Birbeck) granules, were detected in various mesodermal tissues (Kondo 1969, Hoshino et al 1970, Breathnach 1977) and, furthermore, LC granules were found to be present in certain histiocytic cells in histiocytosis X (Basset & Turiaf 1965, Cancilla et al 1967) and occasionally, in malignant ceils of patients with malignant histiocytosis (Imamura et al 1971) and leukemic reticuloendotheliosis (Shamoto et al 1976).…”
Section: Introductionmentioning
confidence: 99%
“…These were 9 cases (7 cases had aggressive clinical course and 2 cases had a benign clinical course.) reported on by Ben-Ezra et al (2), and 9 isolated cases (3-11). Of the 19 cases, including our case, the skin was involved at the time of diagnosis in 9 cases, and the skin was the only organ involved in 3 of the cases.…”
Section: Discussionmentioning
confidence: 91%
“…The lymph nodes, spleen, liver, bone marrow, thymus, lung and kidney were the other organs frequently involved. The heart was involved in two cases (2,3). The age at the time of diagnosis ranged from newborn (2) to 76 yr (7) with the average age being 37.…”
Section: Discussionmentioning
confidence: 99%
“…Imamura et al [10] described a 9-year-old girl with leukemic infiltration of Langerhans' granule-containing histiocytes characterized by indented nuclei and abundant, faintly acidophilic cytoplasm. The initial diagnosis of this patient was acute granulocytic leukemia, because the peripheral WBC count was 69,200 lL -1 , with 62% myeloblast-like, abnormal cells.…”
Section: Discussionmentioning
confidence: 99%